Lettuce for Human Consumption Collected in Costa Rica Contains Complex Communities of Culturable Oxytetracycline- and Gentamicin-Resistant Bacteria - Rodríguez Sánchez, César (2006)
The present widespread use of antimicrobials in crop farming is based upon their successful application in human medicine. However, recent evidence suggests that the massive anthropogenic release of antimicrobials into the biosphere has selected for resistant bacteria and facilitated the transfer of resistance genes among them. This work deals with the examination of iceberg lettuce collected at 10 farms from two regions in Costa Rica. Farmers from nine sampling sites regularly apply commercial formulations containing gentamicin, oxytetracycline, streptomycin, or a combination of them without being able to indicate how often and how much of these products have been sprayed onto the crops. One organic farm was also investigated for comparative purposes. Oxytetracycline- and gentamicin-resistant bacteria were abundantly detected using selective enrichment cultures. Furthermore, colony mixtures from selective plates were characterized by chemotaxonomical and molecular fingerprinting methods. Both types of resistant communities accounted for a significant fraction of all culturable bacteria and included several resistance genes as well as factors for their potential horizontal transfer. Given the fact that lettuce is eaten raw, it may contribute to the dissemination of antimicrobialresistant bacteria and/or their resistance genes from the environment to the microbial biota of the human intestine.